Structural and functional features of human muscle-tendon unit - Finni, T. (Scandinavian Journal of Medicine & Science in Sports, 2006)
This paper reviews the architectural details and the in vivo behavior of the human muscle-tendon unit with the focus on the triceps surae and quadriceps femoris muscles. Recent advances in experimental techniques allow in vivo measurements of muscle-tendon architecture and function. In particular, the use of ultrasonography for measurement of tendon and muscle has expanded our knowledge in the last decade. Furthermore, the nuclear magnetic resonance imaging is opening up new insights not only for three-dimensional anatomical information but also for examining musculo-skeletal motion in vivo. While these two completely non-invasive methods provide kinematic data, in vivo force measurements still require somewhat invasive procedures and are scarce. Thus, muscle forces are frequently calculated using both simple and complex models. These models can give us suggestions for further experimental work. There is a need to examine the experimental data ranging from single-fiber experiments to the muscle function in human movement in order to understand the muscle-tendon function in vivo fully. Furthermore, appreciation of the structure-function relationships may help us to understand the entity of muscle-tendon function both from the perspective of mechanical behavior and neural control.